Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1093/brain/awq287
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, neuroradiological and genetic findings in pontocerebellar hypoplasia

Abstract: Pontocerebellar hypoplasia is a group of autosomal recessive neurodegenerative disorders with prenatal onset. The common characteristics are cerebellar hypoplasia with variable atrophy of the cerebellum and the ventral pons. Supratentorial involvement is reflected by variable neocortical atrophy, ventriculomegaly and microcephaly. Mutations in the transfer RNA splicing endonuclease subunit genes (TSEN54, TSEN2, TSEN34) were found to be associated with pontocerebellar hypoplasia types 2 and 4. Mutations in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
257
0
9

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 205 publications
(292 citation statements)
references
References 26 publications
21
257
0
9
Order By: Relevance
“…Including the two patients we report here, 29 patients with RARS2 mutations are described in literature so far (Namavar et al 2011a;Cassandrini et al 2013;Rankin et al 2010;Glamuzina et al 2012;Kastrissianakis et al 2013;Joseph et al 2014;Li et al 2015;Lax et al 2015;Nishri et al 2016;Ngoh et al 2016;Alkhateeb et al 2016). Splice site, nonsense, or missense mutations are identified throughout the RARS2 gene, but no patients with biallelic null mutations were identified, supporting the assumption that complete abolishment of tRNA-arg would be lethal.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Including the two patients we report here, 29 patients with RARS2 mutations are described in literature so far (Namavar et al 2011a;Cassandrini et al 2013;Rankin et al 2010;Glamuzina et al 2012;Kastrissianakis et al 2013;Joseph et al 2014;Li et al 2015;Lax et al 2015;Nishri et al 2016;Ngoh et al 2016;Alkhateeb et al 2016). Splice site, nonsense, or missense mutations are identified throughout the RARS2 gene, but no patients with biallelic null mutations were identified, supporting the assumption that complete abolishment of tRNA-arg would be lethal.…”
Section: Discussionsupporting
confidence: 66%
“…These patients present with severe mental and motor retardation, progressive microcephaly, and dystonia/chorea (Namavar et al 2011a, b). MR imaging typically shows a "dragonfly" or "butterfly" configuration of the cerebellum (Namavar et al 2011a). New subtypes of PCH, based on differences in phenotypes and/or genotype were described over the past years, and we showed that the same genetic variant can be responsible for different forms of PCH (Namavar et al 2011b).…”
Section: Introductionmentioning
confidence: 70%
“…Large cysts were seen on MRI in one patient at the age of 1 month, located at the lateral aspects of the hemispheres [15]. A further patient was illustrated in a subsequent larger cohort [16]. The overall prevalence of cysts in PCH1 and PCH2 is rather low.…”
Section: Pontocerebellar Hypoplasiasmentioning
confidence: 86%
“…These are characterized by congenital hypotonia, progressive postnatal weakness and areflexia with anterior horn cell degeneration. The differential diagnosis includes X-linked infantile SMA with arthrogryposis (XL-SMA) [4,5], SMA due to mitochondrial dysfunction [6][7][8], SMA with pontocerebellar hypoplasia (SMA-PCH/PCH1) [9][10][11][12][13], and SMAwith respiratory distress (SMARD) ( Table 1) [14][15][16]. SMARD1 (or HMN type VI) is probably the second most commonly encountered pediatric from of SMA due to mutations in IGHMBP2 [14].…”
Section: Smn1-related Smamentioning
confidence: 99%